2004
DOI: 10.1063/1.1841453
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence and polarized photodetection of single ZnO nanowires

Abstract: Single crystal ZnO nanowires are synthesized and configured as field-effect transistors. Photoluminescence and photoconductivity measurements show defect-related deep electronic states giving rise to green-red emission and absorption. Photocurrent temporal response shows that current decay time is significantly prolonged in vacuum due to a slower oxygen chemisorption process. The photoconductivity of ZnO nanowires is strongly polarization dependent. Collectively, these results demonstrate that ZnO nanowire is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
237
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 342 publications
(251 citation statements)
references
References 21 publications
13
237
1
Order By: Relevance
“…Above the band gap energy, the photoconductivity is almost constant (note the semilogarithmic scale) up to the deep UV spectral region, while no photoresponse has been detected in the range from 1.5 to 3.2 eV. The absence of photoconduction upon visible light illumination testifies to the low defect levels, 17,18 such as oxygen vacancies in the ZnO NWs, which is supported by the low intrinsic electron concentration estimated above. The high spectral selectivity combined with high photosensitivity suggest the possibility of using ZnO NWs as "visible-blind" UV photodetectors for commercial, military, and space applications.…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…Above the band gap energy, the photoconductivity is almost constant (note the semilogarithmic scale) up to the deep UV spectral region, while no photoresponse has been detected in the range from 1.5 to 3.2 eV. The absence of photoconduction upon visible light illumination testifies to the low defect levels, 17,18 such as oxygen vacancies in the ZnO NWs, which is supported by the low intrinsic electron concentration estimated above. The high spectral selectivity combined with high photosensitivity suggest the possibility of using ZnO NWs as "visible-blind" UV photodetectors for commercial, military, and space applications.…”
mentioning
confidence: 68%
“…Schematics of the NW energy band diagrams in dark and under illumination are displayed in parts b and c of Figure 2, respectively, illustrating the charge separation process of photogenerated electrons and holes under the intrinsic NW electric field and the occupation of surface states by photogenerated holes. In ZnO, it has been previously shown that the following trapping mechanism is governing the photoconduction in thin films 25 and NWs: 8,9,13,18,[26][27][28] in the dark (Figure 2b), oxygen molecules are adsorbed on the oxide surface and capture the free electrons present in the n-type oxide semiconductor [O 2 …”
mentioning
confidence: 99%
“…Additionally, it is also important to point out that in the particular case of ZnO nanowires the photo absorption spectrum typically has a narrow peak near the band edge in the exciton absorption region. 17,24 Consequently, V th also have its maximum value at the photoabsorption peak due to the highest increase in carrier density. This direct dependence of the V th with the energy of the incident light opens a new application of ZnO phototransistors because the gate voltage can be used to make the device more selective to certain frequencies.…”
Section: Resultsmentioning
confidence: 99%
“…However, in the case of the samples studied here such a ratio -or rather its inverse -is a measure of internal lattice defects relative to the occurrence of chemisorbed oxygen, rather than any meaningful measure of 'crystallinity'. In any case it is clear that for ZC1-4 there is significant emission in the green-red regime (wavelength 475 -600 nm or energy 2.6 -2.1eV), a feature that has important bearing on the wavelength selective photoresponse of ZnO-based detectors [41][42][43][44].…”
Section: Photoluminescencementioning
confidence: 99%